2022
DOI: 10.1088/1757-899x/1226/1/012074
|View full text |Cite
|
Sign up to set email alerts
|

The impact of propulsive architecture on the design of a 19-passenger hybrid-electric aircraft

Abstract: The electrification of aircraft is an on-going endeavor, currently examined intensively in the general aviation class. However, for the commuter class, the proper selection of the hybrid-electric propulsive architecture is instrumental, to fully exploit the electrification benefit. Within this work, a comparison of two 19-seater aircraft with different hybrid-electric propulsive components is made, using an in-house aircraft conceptual design tool. The first aircraft is based on a twin-turboprop parallel-hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…9. Additionally, the kerosene production impact is reduced significantly, compared to the findings in a previous work [10]; however, this reduction is explained by the variation of certain coefficients in the ReCiPe update from 2008 to 2016, where the importance of kerosene production is reduced, compared to 2008.…”
Section: Environmental Impact Assessment Evaluationcontrasting
confidence: 71%
See 1 more Smart Citation
“…9. Additionally, the kerosene production impact is reduced significantly, compared to the findings in a previous work [10]; however, this reduction is explained by the variation of certain coefficients in the ReCiPe update from 2008 to 2016, where the importance of kerosene production is reduced, compared to 2008.…”
Section: Environmental Impact Assessment Evaluationcontrasting
confidence: 71%
“…Considering DOC, there are several methodologies to assess the economic feasibility of propulsive units [13-15], but there is a lack of assessment for smaller aircraft categories, such as the commuter aircraft (19-seater), especially if novel propulsive architectures are considered. Moreover, for the aircraft environmental impact evaluation, previous works indicated that the main contributor to the LCA is aircraft operation [10,15]. However, aircraft electrification brings new challenges and raises new research questions about the subject [16].…”
mentioning
confidence: 99%
“…For aviation fuel, 3.16 kg of are emitted per kg of fuel burnt [1]. In the work of Nasoulis et al [51] the environmental impact of both conventional and hybrid-electric aircraft with different propulsion configurations (i.e., turbofan and turboprop variants) is examined, considering a life cycle analysis for aircraft conceptual design. Additionally, both EU electricity mix and power from renewable sources are considered in the environmental impact single score assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Results from an experiment performed at TU Delft [84] on different architectures show a net force benefit with respect to the free-stream case of about 9% for wake ingestion-i.e., propeller detached from the body, in its wake-and 18% for BLI-i.e., propeller installed on the body stern-with a propeller efficiency improvement of 11% for wake ingestion and of 21% for the BLI configuration, at J = 1. Other works also concluded that BLI can bring sensible to significant emissions reduction [85,86], also on commuter aircraft [87].…”
Section: Boundary Layer Ingestionmentioning
confidence: 95%